Chronic, but not sub-chronic, stress increases binge-like alcohol consumption in male and female c57BL6 mice - McCarthy, William; Huq, Shama N.; Allen, Kristen; Scally, Lindsay; Petri, Avelina; Wujek, Madeline; Sachs, Benjamin D. (Frontiers in Behavioral Neuroscience, 2022)
Stress is known to contribute to mental illness and alcohol use disorders, which are highly prevalent and lead to considerable disability. These stress-related disorders are characterized by significant sex differences that remain poorly understood. Preclinical research comparing the effects of stress in males and females has the potential to provide new insight into the neurobiology of these conditions. The current study compared the effects of chronic vs. sub-chronic exposure to variable environmental stressors on binge-like alcohol consumption using the drinking-in-the-dark model in male and female c57BL6 mice. The results reveal that chronic, but not sub-chronic, exposure to variable stress increases alcohol intake in both sexes. Stress-induced alterations in gene expression were also compared in the nucleus accumbens, a brain region widely known to play a key role in stress susceptibility and reward processing. Real-time PCR data indicate that chronic, but not sub-chronic environmental stress leads to a downregulation of adenosine 2A receptor mRNA. In contrast, sub-chronic stress increased CREB expression, while chronic stress did not. Several sex differences in the effects of stress on gene expression were also noted. Our results demonstrate that reductions in adenosine 2A receptor mRNA in the nucleus accumbens are associated with the increased binge drinking of chronically stressed animals, but future work will be required to determine the functional importance of this gene expression chance. Continuing to define the molecular alterations associated with stress-induced increases in alcohol intake has the potential to provide insight into the development, progression, or treatment of stress-related disorders.